Изучение популяций вредных грызунов агробиоценозов Украины - Сокур, И.Т. (Вестник зоологии, 1971)
Department of ecology of the Institute of Zoology of the Academy of Sciences of
the Ukrainian SSR carries out a complex study of the Microtus arvalis Pal l populations from agrobiocenoces of the Ukraine. The sexual, age and spatial structure of populations, peculiarities of ga s exchange in M. arvalis, some hematological indices and A
and E vitamin content in the rodent liver were studied. A number of males in populations
of the agrobiocenoses is established to decrease with an age of M. arvalis Pall . The
process of the population renewal, i. e. its rejuvenation, is accelerated. An annual alternation of vegetation in the fields prevented From forming stable biocenoses. When the habitats are often changed the mixing of micropopulations takes place, which excludes the inbreeding and increases the physiological heterogeneity of populations.